2020
DOI: 10.4102/phcfm.v12i1.2637
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a video call visit system in a coronavirus disease 2019 unit

Abstract: The lockdown and physical distancing strategies imposed to combat COVID-19 have caused seismic shifts at all levels of society. Hospitals have been particularly affected. Healthcare workers (HCW’s) wore PPE during all patient interactions and visitors were prohibited. Life for a patient became lonelier and for those with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) measures were even more severe. HCW’s must treat patients following a biopsychosocial approach and promote communication between pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…All these studies were reported in 2020 during the COVID 19 outbreak. Two articles were cross‐sectional surveys (Armand et al, 2021 ; Feldman et al, 2021 ), one was a randomized controlled trial (Owolabi et al, 2020 ), one was a news article (Adebayo et al, 2020 ), one was a narrative review from Kenya (Jaguga & Kwobah, 2020 ), two were observational studies (Adebayo et al, 2021 ; Nlemadim et al, 2021 ), two were letters (Balme et al, 2020 ; Moolla et al, 2020 ), one was a commentary (Kamulegeya et al, 2020 ) and the other one was a retrospective and prospective analysis (Moyo & Madziyire, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies were reported in 2020 during the COVID 19 outbreak. Two articles were cross‐sectional surveys (Armand et al, 2021 ; Feldman et al, 2021 ), one was a randomized controlled trial (Owolabi et al, 2020 ), one was a news article (Adebayo et al, 2020 ), one was a narrative review from Kenya (Jaguga & Kwobah, 2020 ), two were observational studies (Adebayo et al, 2021 ; Nlemadim et al, 2021 ), two were letters (Balme et al, 2020 ; Moolla et al, 2020 ), one was a commentary (Kamulegeya et al, 2020 ) and the other one was a retrospective and prospective analysis (Moyo & Madziyire, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most utilized mode of engaging patients was the telephones (P. Adebayo et al, 2020 ; Armand et al, 2021 ; Balme et al, 2020 ; Kamulegeya et al, 2020 ) and (Feldman et al, 2021 ). Two studies made use of the social media platform Whatsapp (Armand et al, 2021 ; Moyo & Madziyire, 2020 ) while some employed virtual platforms and video calls such as Skype (Armand et al, 2021 ; Moolla et al, 2020 ). Telehealth in SSA was not limited to consultation but also extended to education with two studies making use of the virtual digital platform to increase awareness and engage patients (Feldman et al, 2021 ; Jaguga & Kwobah, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…We suggest implementing the use of cell-phones, tablets, personal computers to make calls or video-calls between hospitalized patients and their relatives, which is a practice that turned out to be beneficial for both the families, by promoting the acceptance of the illness, and the patients themselves ( Moolla et al., 2020 ).…”
Section: A Call For Intervention and Prevention Strategiesmentioning
confidence: 99%
“…In one hospital in Cape Town, "video call champions" were appointed in each ward whose role included raising awareness of the video call system and taking primary responsibility for making calls. Family members could visit from home or at the hospital in a separate room via web-based video calls (Moolla et al, 2020).…”
Section: Use Of Information Technology and Social Mediamentioning
confidence: 99%